2011
DOI: 10.1007/s10750-011-0735-z
|View full text |Cite
|
Sign up to set email alerts
|

Importance of water level dynamics for vegetation patterns in a natural percolation mire (Rospuda fen, NE Poland)

Abstract: Although conservation of percolation mires is very important for the European biodiversity, our understanding of their functioning is still insufficient, as most of the studied sites are to some extent degraded. We present a study on the relationship between vegetation patterns, hydrochemical gradients and water level fluctuations carried out in the Rospuda valley (NE Poland), which was recently discovered for science as a uniquely preserved fully functioning percolation mire. Vegetation composition, mire wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 26 publications
(26 reference statements)
0
38
0
Order By: Relevance
“…A previous study by Jabłońska et al (2011) showed, that the chemical composition of subsurface water (sampled from shallower, 0.5 m-deep, piezometers) is quite uniform within the whole Rospuda mire and is not especially useful for distinguishing vegetation types. In the present study we analysed water from the bottom peat layer (in order to minimise influence of external factors), revealing that the two basins may be fed by groundwater from two different aquifers (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…A previous study by Jabłońska et al (2011) showed, that the chemical composition of subsurface water (sampled from shallower, 0.5 m-deep, piezometers) is quite uniform within the whole Rospuda mire and is not especially useful for distinguishing vegetation types. In the present study we analysed water from the bottom peat layer (in order to minimise influence of external factors), revealing that the two basins may be fed by groundwater from two different aquifers (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…At the beginning, vegetation was dominated by (sparse) tall sedge communities, but also scattered trees (Betula, Alnus) could establish, so the peat was, at least periodically, Fig. 1; slope of a mire is presented schematically, for more detailed mire surface levelling, see Jabłońska et al (2011) sufficiently dry to allow growth of trees. The stable ground with underlying sands may also have supported tree growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our understanding of the functioning of intact or pristine systems is still lacking, with the majority of studied sites being to some extent degraded. Jablonska et al (2011) describe the relationship between vegetation patterns, hydrochemical gradients, and water level fluctuations carried out in the Rospuda valley (North East Poland), which was recently discovered as an uniquely-preserved, fully functioning percolation mire.…”
Section: Vegetation In Wetlands and Water Treatmentmentioning
confidence: 99%